Kinetics and mechanism of fretting-corrosion of spark and laser-spark ZrB2-сontaining coatings on VT3-1 alloy / I.A. Podchernyaeva, A.I. Dukhota, V.M. Panashenko, A.D. Panasyuk, A.M. Bloshchanevich, M.A. Vasilkovskaya // Problems of Tribology. – 2012. – - Подчерняева, И.А.; Духота, А.И.; Панашенко, В.М.; Панасюк, А.Д.; Блощаневич, А.М.; Васильковская, М.А. (Problems of Tribology, 2014)
Wear properties of electric spark ZrB2-based ceramic coatings on titanium alloy under dry fretting in a wide range of displacement cycles of (1 … 10)105 have been studied. The coating of ZrB2–ZrSi2–LaB6 ceramic material was found to have the same wear resistance as WC–3% Co hard alloy coating. Laser treatment of ZrB2-based spark coatings additionally increase their wear resistance by 65 - 70 %. The results are discussed taking into account the formation of secondary structures in the contact area.